2008
DOI: 10.1016/j.neuro.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Moderate perinatal arsenic exposure alters neuroendocrine markers associated with depression and increases depressive-like behaviors in adult mouse offspring

Abstract: Arsenic is one of the most common heavy metal contaminants found in the environment, particularly in water. We examined the impact of perinatal exposure to relatively low levels of arsenic (50 parts per billion, ppb) on neuroendocrine markers associated with depression and depressive-like behaviors in affected adult C57BL/6J mouse offspring. Whereas most biomedical research on arsenic has focused on its carcinogenic potential, a few studies suggest that arsenic can adversely affect brain development and neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 52 publications
8
81
2
Order By: Relevance
“…Depressive syndromes have been reported in Gulf War veterans (McDiarmid et al, 2002). Other heavy metals induce also depressive-like behaviors in mouse offspring (Onishchenko et al, 2007;Martinez et al, 2008). It has been suggested that impairment in hippocampal function may be involved in the etiology of depression (Warner-Schmidt and Duman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Depressive syndromes have been reported in Gulf War veterans (McDiarmid et al, 2002). Other heavy metals induce also depressive-like behaviors in mouse offspring (Onishchenko et al, 2007;Martinez et al, 2008). It has been suggested that impairment in hippocampal function may be involved in the etiology of depression (Warner-Schmidt and Duman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of mouse dams to relatively low levels of arsenic (50 µg arsenate/L) during pregnancy and lactation resulted in changes in the neuroendocrine markers associated with depression and depressivelike behaviours in affected adult C57BL/6J mouse offspring (Martinez et al, 2008). The results suggested that perinatal arsenic exposure may disrupt the regulatory interactions between the hypothalamic-pituitary-adrenal axis and the serotonergic system in the dorsal hippocampal formation in a manner that predisposes affected offspring towards depressive-like behaviour.…”
Section: Inorganic Arsenicmentioning
confidence: 98%
“…For example, in utero and early life exposure of rodents even to 50 or 100 μg/μL of iAs through drinking water leads to learning and memory deficits in adult offspring [3,13]. In another study, perinatal mice exposure to low iAs concentration (55 μg/L) led to reduced performance in forced swim test and increased response time in learned helplessness [10]. However the mechanisms underlying such neurotoxic effects that lead to As-associated cognitive dysfunction have not been completely elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…However, stronger evidence from exposed populations and experimental studies have linked iAs exposure with cognitive impairment [5][6][7][8]. In exposed populations, a decreased verbal IQ in a dose-response manner has been reported in children with high urinary As concentration [9], and cognitive impairment was also found in a study conducted with children exposed to low iAs levels [10,11]. In adult populations, a significant correlation between exposure to As and an impaired cognitive ability even at As concentrations below the EPA standards (10 μg/L) for drinking water has been reported also [12].…”
Section: Introductionmentioning
confidence: 99%